Highly sensitive tunable diode laser absorption spectroscopy of CO2 around 1.53 μm - Liu, Yong; Li, Baosheng; Zhai, Yufeng; Wang, An (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
The absolute absorption spectrum intensities of carbon dioxide sample have been recorded with a tunable diode laser spectrometer in the spectral range 6506–6520 cm–1, which is suitable for the in situ sensing of carbon dioxide in the lower stratosphere, and were studied using a commercial telecommunication-type diode laser. The intensity of the weakest line we detected in this experiment is 9.116×10–27 cm–1/(molecule·cm–2) at a pressure of 0.35 torr, and the corresponding absorption is 1.96×10–6 with SNR of 2.67.
Optica Applicata, Vol. 36, 2006, nr 1, s. 15-22
Keywords: optyka; wavelength modulation; diode lasers; absorption spectroscopy